Gestational Diabetes Mellitus and Preeclampsia: Correlation and Influencing Factors - Yang, Ying; Wu, Na (Frontiers in Cardiovascular Medicine, 2022)
Gestational diabetes mellitus (GDM) and preeclampsia (PE) are common pregnancy complications with similar risk factors and pathophysiological changes. Evidence from previous studies suggests that the incidence of PE is significantly increased in women with GDM, but whether GDM is independently related to the occurrence of PE has remained controversial. GDM complicated by PE further increases perinatal adverse events with greater impact on the future maternal and offspring health. Identifying factors affecting PE of GDM, specifically those that are controllable, is important for improving pregnancy outcomes. This paper provides the findings of a review on the correlation between GDM and PE, factors influencing PE development in GDM, possible mechanisms, and predictive markers. We conclude that GDM is an independent risk factor for the development of PE in singleton pregnancy, and optimizing the treatment and management of GDM can reduce the incidence of PE, which is very helpful to improve pregnancy outcomes.